ENT 600 : Sharp Coporation/ Muhammad Syahiir Hamadan @ Hamdan - Hamadan @ Hamdan, Muhammad Syahiir (2021)
This writing mainly talked about analysis problems from product made of Sharp Corporation and recommends the best solution on how to deal with the forces. Student will learn about real-life situation where existing problems need to be solved. While application of theories and concepts learned in class to real-life situation, student need to improve understanding and enhance knowledge from the experience of real company. From the problem that chosen company did and the solution they take, student should think critically to improve problem-solving and decision-making skill just like their own company. With the theories that learn in class, student can do the analysis of the situation where problems need to be solved and chance need to be taken. Sharp Corporation Company is chosen as it is well known as company produce product for customer demand. Sharp is the japan electronic manufacturer with a reputation for building great product at budget-friendly prices. Sharp Corporation is one of the worldwide companies that produce electronic product and has many branches around Asia and Europe. One of product that attracts me to improve is their single-serve blender, EM131BK. Blender is advance technology to grind ingredients while the traditional way using stone mortar. This blender was ensuring about consumer safety. Consumer will experienced using high-powered motors while come with extra set to done thing easily.